Poverty reduction through women employment in farms and rice mills in an area of Dinajpur district - Rahman, MS; Hasan, MR (Journal of the Bangladesh Agricultural University, 2011)
The study was undertaken to examine the socio-economic profiles of women participated in farms and rice mills activities; to examine contribution of women to household income which reducing their poverty; to identify the factors influencing the level of family income in farms and rice mills labourers; and to identify the problems and constraints of farms and rice mills. Bochagonj Upazila of Dinajpur district was selected purposively for the study considering the availability of large number of farm and rice mill labourers. Sixty samples of each category have been selected by random sampling procedure and primary data were collected by direct interview through a pre-tested survey schedule. The educational status, land holding and other household assets position were improved due to the women’s contribution to overall family income. Patterns of family expenditure remained same before and after the women involvement in farm and rice mill works but increased over time that indicated some significant changes in the level of poverty of the households. Age of the respondents, family size, land holding, number of earning members and respondents’ income contributed significantly to the variability of income and employment. Major problems were nature of the work and the variation in the salary level between male and female labourers. Finally, women contributed a small amount but a significant proportion of their family income and the socioeconomic status of the women farm and rice mill labourers should be improved through direct participation in income generating activities by reducing the male and female discriminations. Keywords: Poverty; Women employment; Farm; Rice mills; Income DOI: http://dx.doi.org/10.3329/jbau.v9i1.8755 JBAU 2011; 9(1): 131-139